Planet Earth - Chancellor, Deborah (New York : Kingfisher, 2006)
Presents an introduction to planet Earth, in simple text with illustrations, providing information on the water cycle, weather and climate, oceans, earthquakes, volcanoes, deserts, forests, and more. Includes activity projects.
Includes index.
4.8
K-3
K-3
Science Books & Films (A.A.A.S.)
Keywords: Earth -- Juvenile literature; Earth sciences -- Juvenile literature; Earth; Earth sciences; Earth; Earth sciences